Acute hepatopancreatic necrosis disease in cultured shrimp in Malaysia - Devadas, Sridevi (2019)
Acute hepatopancreatic necrosis disease (AHPND) is caused by a unique strain of Vibrio parahaemolyticus (VpAHPND) containing a highly pathogenic ~69 kbp (pVA1) plasmid encoding homologous of the Photorhabdus insect-related (Pir) binary toxins, PirAvp and PirBvp. This plasmid is self-transmissible and has also been found in Vibrio harveyi, Vibrio campbellii, Vibrio punensis and Vibrio owensii. The Penaeus vannamei and Penaeus monodon are the species susceptible to AHPND. Nevertheless, there is an increase in the cultivation of P. monodon in Malaysia, indicating that the species might have shown better survival to AHPND. Therefore, early detection and genome studies of the VpAHPND are essential to control the spread of the disease and to understand the biodiversity of the strain in farmed penaeid shrimp. The VpAHPND has also been discovered carrying the tetracycline resistance (tetB) gene. There is lack of information about the presence of tetracycline resistant VpAHPND in Malaysian aquaculture. Moreover, the available AHPND polymerase chain reaction (PCR) methods detect up to only two genes and thus is unable to confirm the VpAHPND and tetB gene in a single PCR reaction. The present work was conducted to isolate and identify the VpAHPND from the cultured penaeid shrimp and subsequently used to evaluate the tolerance of a commercially available Madagascar-Malaysia crossbred P. monodon and to develop an improved rapid detection method for AHPND. An AHPND infected farm culturing crossbred P. monodon was sampled for the isolation of VpAHPND. The isolate was subsequently used to challenge the healthy crossbred P. monodon via immersion and per os (feeding) treatments. Following that, a 5-plex PCR method was optimized for the detection of pirAvp, pirBvp, thermolabile hemolysin (tlh), transmembrane regulatory protein (toxR) or tetB and 16S ribosomal RNA (16s rRNA) genes. The 5-plex PCR method was evaluated using VpAHPND and Vibrio isolates obtained from the crossbred P. monodon and farmed P. vannamei respectively followed by sensitivity and specificity tests. All VpAHPND were then analyzed for antibiotic susceptibility to six types of antibiotics. Following that, the VpAHPND isolated from the crossbred P. monodon and farmed P. vannamei were sequenced for draft genome comparison. Three VpAHPND were succesfully isolated from the AHPND infected farmed crossbred P. monodon. The laboratory challenge of the healthy crossbred P. monodon satisfied the Koch’s Postulates. Nevertheless, challenged shrimp failed to show AHPND gross clinical signs within 48 h post infection (p.i.). The histopathology analysis of shrimp challenged by immersion showed severe necrosis of the hepatopancreas (HP) cells within 24 h p.i. However, the shrimp challenged by immersion and per os treatments showed higher survival of 66.7 % and 53.3 % respectively over a longer duration of 10 days p.i. During the evaluation of 5-plex PCR method, five tetracycline resistant VpAHPND were detected and isolated from the farmed P. vannamei. The sensitivity and specificity tests of the 5-plex PCR, showed that the method allows rapid, sensitive (10 pg/μL), specific and reliable detection of VpAHPND or tetracycline resistant VpAHPND. The VpAHPND isolated from both farmed penaeid shrimp were resistant to bacitracin, vancomycin and streptomycin. Furthermore, the draft genome analysis confirmed that the VpAHPND strains contained a pVA1-like plasmid encoding the pirAvp and pirBvp genes as well as several antibiotic resistance genes. The isolated VpAHPND strains also displayed > 98% similarity to VpAHPND originating from Thailand, Mexico and Vietnam. In conclusion, this study has successfully isolated, identified and sequenced multiple antibiotics resistant VpAHPND from the crossbred P. monodon and farmed P. vannamei. The study also illustrated that the crossbred P. monodon has longer survivability and tolerance to AHPND for 10 days p.i. In addition, a new and improved 5-plex PCR method has been successfully develop for rapid identification of the VpAHPND and tetracycline resistant VpAHPND in a single PCR reaction.